Response to Galcanezumab in a Patient with Complex Neuropsychiatric Comorbidity: A Case Report - Anna Anselmo; Maria Pagano; Francesco Corallo; Irene Cappadona; Rosario Grugno; Domenico Cosenza; Gianluca Vita; Riccardo Lo Presti; Davide Cardile; Viviana Lo Buono; Rocco Salvatore Calabrò (Journal of Clinical Medicine, 2026)
Background: Migraine is a leading cause of disability worldwide and is frequently associated with psychiatric comorbidities that may influence pain perception and treatment response. Anti-CGRP monoclonal antibodies represent an effective preventive treatment, although response variability remains poorly understood, particularly in patients with complex neuropsychiatric profiles. Case Presentation: We report the case of a 49-year-old woman with migraine with a previously chronic course and psychiatric comorbidity, including bipolar disorder and obsessive–compulsive disorder, treated with galcanezumab. The clinical course was characterized by an “on-off-on” pattern, with marked worsening after treatment discontinuation and subsequent improvement after treatment reintroduction. Results: The patient presented with severe emotional distress (BDI-II = 59; STAI = 77–80), a very high self-reported burden of central sensitization-related symptoms (CSI = 100/100) and reduced performance on cognitive screening measures (MoCA = 19/30; BCSE = 18/58). MMPI-3 findings indicated a high level of self-reported psychological distress; however, substantial elevations in symptom-validity indicators required cautious interpretation of the substantive scales. Conclusions: This case illustrates that complex neuropsychiatric comorbidity and psychotropic polypharmacotherapy did not preclude an apparent clinical benefit from galcanezumab. Treatment discontinuation and reintroduction were temporally associated with worsening and subsequent improvement in headache frequency, although causality cannot be established from a single uncontrolled observation. The case also highlights the potential value of coordinated neurological and psychiatric monitoring in patients with migraine and complex neuropsychiatric profiles.